LEGAL PROTECTION OF DOCTORS IN PROVIDING HEALTH SERVICES - Bambang Tri Bawono (UNISSULA, 2020)
Cases of alleged malpractice committed by doctors or health workers have become an interesting issue that has been widely discussed by the public. Malpractice is basically due to the emergence of differences in perception between patients and doctors or health workers. The research method used in this study is library research, library research limits its activities to library collections. While the approach used in this study is normative juridical, the results of the study mentioned that the standards that must be met by doctors to obtain legal protection are professional standards, operational procedures standards, and medical service standards. These three standards, doctors are also obliged to make informed consent as part of health service standards, and carry out the obligations as contained in Article 51 of Law No. 29 of 2004 concerning Medical Practice. In addition, doctors can be free from allegations of medical malpractice when providing health services in accordance with professional standards and operational procedures, providing medical services based on informed consent and the principle of non-vit inura volenti law or the assumption of risk, respectable minority rules and error of in judgment, as well as contribution negligence.